A novel approach to improving coagulation sample ordering in an emergency department. Issue 1 (11th February 2015) - Murphy, Emma; MacGlone, Sile; McGroarty, Claire
Abstract: Driven by emergency department targets, there is a need for rapid initial assessment and investigations of attendees to the department, and blood tests are often performed before full patient assessment. It has been shown that many investigations ordered in the emergency department are inappropriate. Coagulation samples are acknowledged as one the commonest blood samples requested on admission. We predicted that the majority of the routine coagulation samples performed in our ED department were unnecessary. We aimed to determine if coagulation tests sent from our department were appropriate, develop guidance for appropriate testing and to increase the percentage of appropriate tests to 90%. Criterion based audit was used. All coagulation samples sent from the ED over a one week period were reviewed and the indications for testing compared to guidance developed by consensus with ED consultants. On the first data collection, 66 of 369 (17%) samples were deemed appropriate. Feedback to clinical staff was given at educational meetings and appropriate indications discussed. In collaboration with both senior nursing and medical staff, coagulation screen request bottles were removed from the main clinical area and were only available in the resuscitation area. Following these interventions, 69 of 97 (71%) samples were deemed appropriate and a further intervention is planned to reach our standard. This improvement could lead to a £100, 000 saving annually and a cross-site collaborative study is planned to spread these improvements.